Evaluation of regional limb perfusion with erythromycin using the saphenous, cephalic, or palmar digital veins in standing horses. Issue 5 (14th December 2012) - Kelmer, G.; Martin‐Jimenez, T.; Saxton, A. M.; Catasus, C.; Elliot, S. B.; Lakritz, J.
Abstract : There are no reported studies evaluating the use of erythromycin for regional limb perfusion (RLP) in horses. Our hypothesis was that using the cephalic and saphenous veins for RLP will enable delivery of therapeutic concentrations of erythromycin to the distal limb. Nineteen healthy horses participated in the study. The cephalic, saphenous or palmar digital (PD) vein was used to perfuse the limb with erythromycin. Synovial samples were collected from the metacarpo/metatarso‐phalangeal (MCP/MTP) joint and blood samples were collected from the jugular vein. Maximum concentration ( C max ) of erythromycin in the MCP joint using the cephalic vein was 113 mg/L. The C max of erythromycin in the MTP joint using the saphenous vein was 38 mg/L. Erythromycin administered using the PD vein was not detectable in the MCP/MTP joint of four of six horses. Concentrations of erythromycin achieved in the synovial fluid of the MCP/MTP joint were between 152 and 452 times the minimal inhibitory concentration (MIC) for Rhodococcus equi ( R. equi ). In conclusion, the results indicate that when using the saphenous or cephalic veins for RLP, therapeutic concentrations of erythromycin in the MTP/MTP joint can be consistently reached.